2016
DOI: 10.1007/s11698-016-0143-8
|View full text |Cite
|
Sign up to set email alerts
|

The stability of money demand in the long-run: Italy 1861–2011

Abstract: Money demand stability is a crucial issue for monetary policy efficacy, and it is particularly endangered when substantial changes occur in the monetary system. By implementing the ARDL technique, this study intends to estimate the impact of money demand determinants in Italy over a long period (1861-2011) and to investigate the stability of the estimated relations. We show that instability cannot be excluded when a standard money demand function is estimated, irrespectively of the use of M1 or M2. Then, we ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Among others, the objective of their work was to ascertain the effect of a change in the currency regime on the monetary aggregates and provide a valid empirical model that would serve as a viable tool for policy performance. Daniele et al (2017), following the application of recent econometric technique auto regressive distributed lags (ARDL), examine the stability of money demand in Italy for the period 1861-2011. The results of their work have shown that instability cannot be ruled out when a function of money demand is assessed irrespective of the use of M1 or M2.…”
Section: Literature Review Of the Money Demand Stability In Italian Economymentioning
confidence: 99%
“…Among others, the objective of their work was to ascertain the effect of a change in the currency regime on the monetary aggregates and provide a valid empirical model that would serve as a viable tool for policy performance. Daniele et al (2017), following the application of recent econometric technique auto regressive distributed lags (ARDL), examine the stability of money demand in Italy for the period 1861-2011. The results of their work have shown that instability cannot be ruled out when a function of money demand is assessed irrespective of the use of M1 or M2.…”
Section: Literature Review Of the Money Demand Stability In Italian Economymentioning
confidence: 99%
“…First generation models based on low frequency data rely on liquidity theory of money demand. Following a number of earlier studies (see, e.g., Baharumshah, Mohd, & Masih, 2009; Bahmani‐Oskooee, Bahmani, Kones, & Kutan, 2015; Daniele et al, 2017; Shafiq & Malik, 2018; Folarin & Asongu, 2019), this study considers augmented money demand function on the basis of Liquidity preference theory. Hence, we start with a standard money demand function where real money demand is assumed to be a function of real income ( Y t ) and interest rate ( r t ) as opportunity cost variable. ()MtPt=L(),Ytrt …”
Section: Methodsmentioning
confidence: 99%
“…Bahmani (2013) estimated positive impact of exchange rate volatility on real broad money demand in the case of 15 less developing countries. Daniele, Foresti, and Napolitano (2017) considered exchange rate volatility and declared it as potential determinant to obtain stable money demand function for Italy. A number of other studies (e.g., Arize, Malindretos, & Grivoyannis, 2005;Bahmani-Oskooee & Ng, 2002;Choi & Oxley, 2004;Higgins & Majin, 2009;Klein, 1977;Laidler, 1980;Nia, Izadi, & Tafti, 2014) may be pointed out where significant role of inflation uncertainty in MDF was found for various developing as well as developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…The paper recommends against switching to interest rate targeting policy in place of money targeting policy. Daniele, Foresti, and Napolitano (2017) apply ARDL technique to test the stability of MDF for Italy. The empirical results conclude that while estimating standard MDF, instability cannot be excluded in broad and narrow definitions of money.…”
Section: Studies Related To Developed Countriesmentioning
confidence: 99%